Protective effect and mechanism of Qingfei Paidu decoction on myocardial damage mediated by influenza viruses - Du, Lijuan; Zhao, Jing; Xie, Nanxi; Xie, Huangze; Xu, Jiating; Bao, Xiaoming; Zhou, Yingsong; Liu, Hui; Wu, Xiao; Hu, Xin; He, Tianyi; Xu, Shujun; et al. (Frontiers in Pharmacology, 2024)
More attention has been paid to myocardial damage mediated by single-stranded RNA virus. Qingfei Paidu Decoction (QFPDD) has been proved to protect the damage of influenza virus A/PR/8/1934 (PR8), but the specific mechanism is unclear. Molecular biological methods together with network pharmacology were used to analyze the effects and underlying mechanism of QFPDD treatment on PR8-induced myocardial damage, to obtain enlightenment on the treatment of COVID-19-mediated myocardial damage. Increased apoptosis and subcellular damage were observed in myocardial cells of the mice infected by PR8. QFPDD treatment significantly inhibited the apoptosis and subcellular damage induced by PR8 virus. The inflammatory factors IFN-β, TNF-α and IL-18 were statistically increased in myocardia of the mice infected by PR8, and the increase of inflammatory factors was prevented by QFPDD treatment. Furthermore, the expression levels or phosphorylation of necroptosis related proteins RIPK1, RIPK3 and MLKL were abnormally elevated in the group of infected mice, while QFPDD restored the levels or phosphorylation of these proteins. Our study demonstrated that HIF-1α is a key target of QFPDD in the treatment of influenza virus-mediated injury. HIF-1α was significantly increased by PR8 infection. Both knockdown of HIF-1α and treated the myocardia cell with QFPDD significantly reversed the increased inflammatory factors during infection. Overexpression of HIF-1α reversed the inhibition effects of QFPDD on cytokine expression. Meanwhile, 7 compounds from QFPDD may target HIF-1α. In conclusion, QFPDD can ameliorate influenza virusmediated myocardium damage by reducing the degree of cell necroptosis and apoptosis, inhibiting inflammatory response and the expression of HIF-1α. Thus, our results provide new insights into the treatment of respiratory virus mediated myocardium damage.